ASUHAN KEPERAWATAN KELUARGA BAPAK S KHUSUSNYA BAPAK S DENGAN MASALAH KESEHATAN DIABETES MELLITUS DI WILAYAH RT 04 RW 07 KELUHAN LIMO KOTA DEPOK - A'tina Hubbaka (2023)
This study aims to investigate nursing care in dealing with Mr. S, especially in overcoming the health problems of diabetes mellitus in the RT 04 RW 07 area of Limo Village. This research used a qualitative approach with a single case study design. Information was obtained through interviews, observation, and document analysis. The results showed that Mr. S's family faced a number of challenges in managing diabetes mellitus. Factors such as lack of knowledge about the disease, unhealthy diet, and limited access to health resources, affect the family's ability to provide appropriate care. Nursing interventions include education on diabetes mellitus management, healthy diet planning, medication management, and development of monitoring and self-care skills. In addition, the role of mentoring and emotional support to the family was also identified as an important factor in helping Mr. S overcome his health problems. In conclusion, nursing care plays a crucial role in helping Mr. S's family overcome the problem of diabetes mellitus. A holistic approach is needed, involving the family in the planning and implementation of care, and providing continuous support. This study is expected to provide a deeper understanding of the challenges faced by families in managing diabetes mellitus, so that it can provide a foundation for the development of more effective nursing interventions in the future. Keywords: nursing care, diabetes mellitus, Mr. S